2007
DOI: 10.1073/pnas.0609364104
|View full text |Cite
|
Sign up to set email alerts
|

WD40 protein Mda1 is purified with Dnm1 and forms a dividing ring for mitochondria before Dnm1 in Cyanidioschyzon merolae

Abstract: Mitochondria are not produced de novo but are maintained by division. Mitochondrial division is a coordinated process of positioning and constriction of the division site and fission of double membranes, in which dynamin-related protein is believed to mediate outer membrane fission. Part of the mitochondrial division machinery was purified from M phase-arrested Cyanidioschyzon merolae cells through biochemical fractionation. The dynaminrelated protein Dnm1 was one of the two major proteins in the purified frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…For studies of mitochondrial division, the cell cycle in C. merolae cells can be synchronized. The proteins that form mitochondrial division rings have been purified and identified (Yoshida et al, 2006;Nishida et al, 2007). C. merolae has two mitochondrial division proteins, an FtsZ homolog (CmFtsZ1) and a ZapA-like protein (ZED), that are similar to bacterial cell division proteins (Takahara et al, 2000;Yoshida et al, 2009).…”
Section: Mitochondrial Fission Proteins In Yeast Animals and A Red mentioning
confidence: 99%
“…For studies of mitochondrial division, the cell cycle in C. merolae cells can be synchronized. The proteins that form mitochondrial division rings have been purified and identified (Yoshida et al, 2006;Nishida et al, 2007). C. merolae has two mitochondrial division proteins, an FtsZ homolog (CmFtsZ1) and a ZapA-like protein (ZED), that are similar to bacterial cell division proteins (Takahara et al, 2000;Yoshida et al, 2009).…”
Section: Mitochondrial Fission Proteins In Yeast Animals and A Red mentioning
confidence: 99%
“…Antibodies against Dynamin 1 (Dnm1), Dynamin 2 (Dnm2), Mda1, a-tubulin, CENH3 and mitochondrial porin were used as previously described Miyagishima et al, 2003;Nishida et al, 2005;Maruyama et al, 2007;Nishida et al, 2007;Fujiwara et al, 2009). Secondary antibodies used for immunofluorescence were, Alexa Fluor 488 or Alexa Fluor 555 goat anti-guinea pig, anti-mouse or anti-rabbit IgG, highly cross-adsorbed (Molecular Probes, Eugene, OR).…”
Section: Antibodiesmentioning
confidence: 99%
“…Dnm1 is one of only two dynamins (Dnm1 and Dnm2) encoded in the C. merolae genome (7,11). Dnm1 and Dnm2 are important components of the mitochondrion-dividing (MD) machinery (9,14,15) and plastiddividing (PD) machinery (16,17), respectively. Immunoblot analysis indicated that Dnm1 was concentrated in the dividing-peroxisome fraction with catalase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6C). Fifth, the width of the filamentous ring in the POD machinery remained constant during peroxisome contraction, whereas those of the MD and PD machineries increased during contraction (8,15) (Figs. S6).…”
Section: Function Of the Pod Machinery And Comparisons Between The Podmentioning
confidence: 99%